Lung Cancer Cells Infiltration into a Mandibular Follicular Cyst - Stefano Marelli; Martina Ghizzoni; Matteo Pellegrini; Andrea Scribante; Gioacchino D’Ambrosio; Domenico Sfondrini (Case Reports in Dentistry)
Introduction. The oral cavity is a rare site for other organs’ tumor metastases. The incidence rate ranges from 1% to 3% of all oral malignancies. Metastases more frequently localize in the mandible, especially in the molar area. Metastases within odontogenic cysts are extremely rare, thus in the literature, only a few cases have been reported. The follicular cyst is one of the most frequent cysts of the jaws. Radiologically it shows as a unilocular lesion with a sclerotic border, characterized by a homogenous radiolucency that incorporates the crown of the unerupted tooth. Methods. A 76-year-old female patient, affected by stage IV of lung adenocarcinoma, reported pain on the left mandible border, alongside lip dysesthesia. The ortho-panoramic radiograph showed a follicular cyst in the posterior left side of the mandible, with involvement of the ascending branch region. The cyst was surgically removed together with the impacted tooth. A histopathological examination of the specimen confirmed the diagnostic suspect of a follicular cyst, but in the cystic wall, focal infiltration of epithelial neoplastic cells was also found. The immunohistochemical analysis showed the presence of three different markers: CK 7+, TTF1+/−, and P40−. These markers identify the cells as metastatic lung carcinoma. Results. Secondary tumor spreading in the jaws’ area is rare (3% of all malignant lesions). Despite odontogenic cysts can undergo a dysplastic transformation (affecting the epithelial covering in ≤1% of the cases), infrequently these neoplastic cells can be related to secondary tumor spreading in a cystic wall. This report describes a metastatic localization within a mandibular follicular cyst. Conclusions. Malignant cancers’ metastasis in the oral district remains a rare and unexplored condition, especially when metastases are located in odontogenic cysts. In this circumstance, surgical removal and histopathological examination are strongly recommended.